2000
DOI: 10.1046/j.1365-2982.2000.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased mast cells in the irritable bowel syndrome

Abstract: Mast cells (MC) release potent mediators which alter enteric nerve and smooth muscle function and may play a role in the pathogenesis of the irritable bowel syndrome (IBS). The aim of this study was to determine if MC were increased in the colon of IBS patients compared to controls. Biopsy specimens were obtained from the caecum, ascending colon, descending colon and rectum of 28 patients: 14 IBS (Rome criteria); seven normal; and seven inflammatory controls. Tissue was stained immunohistochemically using a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
319
2
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 422 publications
(354 citation statements)
references
References 58 publications
24
319
2
9
Order By: Relevance
“…Further studies should clarify whether the elimination diet can improve the previously demonstrated mast cell mucosal inflammation and the neural damage which has been reported in IBS. 3,4,[7][8][9] In fact, the relationship between FH and dismotility in pediatric patients has been clearly demonstrated. 20,[33][34][35] ECP might be as useful in FH patients as it is in patients with respiratory allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies should clarify whether the elimination diet can improve the previously demonstrated mast cell mucosal inflammation and the neural damage which has been reported in IBS. 3,4,[7][8][9] In fact, the relationship between FH and dismotility in pediatric patients has been clearly demonstrated. 20,[33][34][35] ECP might be as useful in FH patients as it is in patients with respiratory allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In support, IBS patients also show increased number and reactivity of mast cells. 28,29 Data from peripheral blood mononuclear cells, as well as in mucosal biopsies, from IBS patients show that cytokines levels including TNF-α, IL-1β and IL-6 are increased in IBS. [30][31][32][33] It is well recognized that proinflammatory cytokines can alter neurotransmitter release within the enteric nervous system to alter motility, secretion, and epithelial permeability via tight junction dysregulation to alter visceral sensitivity.…”
Section: Pathophysiology Of Irritable Bowel Syndrome: Activation Of Tmentioning
confidence: 99%
“…4 MCs hyperplasia and activation lead to abnormal gastrointestinal sensitivity, motility, and secretion, which in turn contribute to the hallmark symptoms of IBS-abdominal pain and/or discomfort, bloating, and abnormal bowel function (diarrhea and/or constipation). 5 Moreover, therapies targeting mast cells, such as mast cell stabilizers (cromoglycate and ketotifen) and antagonists of histamine and serotonin receptors, have been tried in IBS patients in several studies, and partially exhibited good efficacy in symptom improvement. 6,7 It further supported the key role of MCs in the process of IBS.…”
Section: Introductionmentioning
confidence: 99%